SCADA development for the microgrid using universal windows platform (phase 1) - Chua, Jian Ming (Nanyang Technological University, 2023)
Microgrid management and performance optimization depend heavily on Supervisory Control and Data Acquisition (SCADA) systems. The SCADA for the microgrid in Clean Energy Research Laboratory is currently operating on an older version of LabVIEW 2015, which could make it incompatible with emerging technology. An overview of the SCADA, including its architecture, is discussed in this report’s first section, along with the feasibility of using the Universal Windows Platform (UWP). The creation of the UWP application is discussed in the second section. The application's architecture and implementation, including the graphical user interface and data visualization, are also covered in detail in this section. The report concludes with the development process and suggestions for future work.